UKRVO – FEATURES AND COMPARISON OF THE NEW CATALOGUE OF PHOTOGRAPHIC SURVEY OF THE NORTHERN SKY - Protsyuk, Yu.; Relke, E. (Одеські астрономічні публікації, 2016)
UkrVO plate archives contain information obtained at different observatories for a long time. With using data of photographic survey of the northern sky (FON project, from -4° to 90°) in Main Astronomical Observatory of NationalAcademyofScience(MAO) new catalogue of positions and magnitudes was obtained. The catalogue contains coordinates and magnitudes of more than 19 million stars and galaxies from 3m to 17.5m for the mean epoch of 1988.3. Comparison with the catalogues UCAC4, PPMX, XPM was carried out. The differences of common stars positions between catalogues are from 0.05"-0.06" for the 9- 11m stars to 0.30"-0.40" for the 5-7m and 15-16m stars. The differences of common stars B-magnitudes between catalogues are from 0.05m-0.10m for the 10-11m stars to 0.4m-0.5m for the 6-7m and 15-16m stars. The obtained results suggest the advisability of using the new catalogue for improving proper motions of stars within the range of 8m-14m magnitudes.